2001
DOI: 10.1177/00912700122012823
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Tolerability of Buspirone during Oral Administration to Children and Adolescents with Anxiety Disorder and Normal Healthy Adults

Abstract: A 21-day, open-label, multisite, dose escalation study comprising three demographic groups (children, adolescents, and adults) was performed to determine the pharmacokinetics and tolerability of orally administered buspirone. Thirteen children and 12 adolescents with anxiety disorder and 14 normal healthy adults were escalated from 5 to 30 mg buspirone bid over the 3-week study. Pharmacokinetic analysis revealed that buspirone was rapidly absorbed in all study groups, reaching peak levels at about 1 hour after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…In these studies that utilized 15–60 mg of buspirone per day, no significant differences between buspirone and placebo were noted for GAD symptoms [BMS, 2010]. In addition, pharmacokinetic studies of this agent revealed plasma exposure to buspirone (and its active metabolite, 1‐(2‐pyrimidinyl)‐piperazine, [1‐PP]) were equivalent or greater in pediatric patients than in adults …”
Section: Neuropharmacology Of Pediatric Gadmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies that utilized 15–60 mg of buspirone per day, no significant differences between buspirone and placebo were noted for GAD symptoms [BMS, 2010]. In addition, pharmacokinetic studies of this agent revealed plasma exposure to buspirone (and its active metabolite, 1‐(2‐pyrimidinyl)‐piperazine, [1‐PP]) were equivalent or greater in pediatric patients than in adults …”
Section: Neuropharmacology Of Pediatric Gadmentioning
confidence: 99%
“…In addition, pharmacokinetic studies of this agent revealed plasma exposure to buspirone (and its active metabolite, 1-(2-pyrimidinyl)-piperazine, [1-PP]) were equivalent or greater in pediatric patients than in adults. [42]…”
Section: Buspironementioning
confidence: 99%
“…One open trial in youth with a variety of anxiety disorders showed significant improvements in anxiety ratings and minimal side effects [76]. An industry-sponsored clinical trial showed that buspirone may be better tolerated at lower doses in anxious children (5-7.5 mg twice daily) than anxious adolescents (5-30 mg twice daily) [77]. Common side effects were lightheadedness, headache, and dyspepsia.…”
Section: Other Medicationsmentioning
confidence: 99%
“…Exposure to PmP was dose-proportional, and the variability in buspirone pharmacokinetics was so wide that no firm conclusions could be drawn regarding nonlinearity of this drug in these populations [94]. Exposure to PmP was dose-proportional, and the variability in buspirone pharmacokinetics was so wide that no firm conclusions could be drawn regarding nonlinearity of this drug in these populations [94].…”
Section: Other Variables Affecting the Metabolite-to-parent Drug Ratiomentioning
confidence: 99%